468. Delayed Mortality Among Solid Organ Transplant Recipients Hospitalized for Covid-19: An International Multicenter Study. (4th December 2021) - Heldman, Madeleine R; Kates, Olivia S; Rakita, Robert M; Lease, Erika D; Limaye, Ajit P; Fisher, Cynthia E
Abstract: Background: Studies of solid organ transplant recipients (SOTr) hospitalized for Covid-19 have focused on short-term outcomes with approximately 30 days of follow-up time. Intermediate-term mortality and associated risk factors for intermediate-term death have not previously been reported. Methods: Using data from a multi-center registry, we assessed mortality by 90 days among SOTr hospitalized for Covid-19 between 3/1/2020 and 12/31/2020. Multivariable Cox-proportional hazard models were used to compare risk factors for mortality by 28 and 90 days. Covariates were selected a priori based on known predictors of death in SOTr hospitalized for Covid-19. All patients were followed for 90 days or were censored at the time of death or last clinical contact, if this occurred prior to day 90 after diagnosis. Results: Among SOTr hospitalized for Covid-19, 198/979 (20%) died within 90 days of diagnosis and 37/198 (19%) of deaths occurred between days 29 and 90. Risk factors for mortality by day 90 days included age >65 years (1.8, 95% CI 1.3-2.4, P < 0.001), lung transplant (compared to non-lung) (1.6, 95% CI 1.1-2.4, P =0.02), chronic lung disease (2.2, 95% CI 1.5-3.4, P =0.002) and heart failure (1.9, 95% CI 1.2-2.9), which were similar to risk factors reported for 28-day mortality (Table 1). Diagnosis during the second half of 2020 (6/20-12/31/20) was associated with lower mortality by 28 days (aHR 0.7, 95% CI 0.5-1.0, P =0.03) compared to diagnosis during the early half of 2020 (3/1-6/19/20); however, mortality by 90 days was similar in the late and early time periods (aHR 0.9, 95% CI 0.7-1.2, P =0.54). Obesity and mTOR inhibitor use were also associated with death by 28 but not 90 days. Kaplan-Meier survival curves by time period of diagnosis are shown in Figure 1. Table 1. Multivariable Cox-Proportional Hazard Model for Mortality at 28 and 90-days Among Solid Organ Transplant Recipients Hospitalized for Covid-19 (N=979) Figure 1. Survival among SOT recipients hospitalized for Covid-19 by diagnosis time period Vertical tick marks represent censored cases. Early 2020 refers to cases diagnosed between March 1 and June 19, 2020 and late 2020 refers to cases diagnosed between June 20 and December 31, 2020. Conclusion: Approximately 20% of deaths among SOTr hospitalized for Covid-19 occurred between days 29 and 90. Future investigations are required to discern the mechanism(s) for the improvement in early, but not late, mortality among SOTr with Covid-19 during the course of the pandemic. Disclosures: Madeleine R. Heldman, MD, Cigna Lifesource (Other Financial or Material Support, Speaking honoraria)Thermo Fisher Scientific (Other Financial or Material Support, Speaking honoraria) Olivia S. Kates, MD, Merk (Scientific Research Study Investigator) Ajit P. Limaye, MD, astellas (Scientific Research Study Investigator)CTI (Scientific Research Study Investigator)GSK (Consultant)Johnson&Johnson (Other Financial or Material Support, Adjudication Committee)merck (Consultant, Grant/Research Support, Scientific Research Study Investigator)moderna (Scientific Research Study Investigator)Novartis (Other Financial or Material Support, DMC member)Novo Nordisk (Consultant)